More than microglia: myeloid cells and biomarkers in neurodegeneration - Kodosaki, Eleftheria; Bell, Rosie; Sogorb-Esteve, Aitana; Wiltshire, Katharine; Zetterberg, Henrik; Heslegrave, Amanda (Frontiers in Neuroscience, 2024)
The role of myeloid cells (granulocytes and monocytes) in neurodegeneration and neurodegenerative disorders (NDD) is indisputable. Here we discuss the roles of myeloid cells in neurodegenerative diseases, and the recent advances in biofluid and imaging myeloid biomarker research with a focus on methods that can be used in the clinic. For this review, evidence from three neurodegenerative diseases will be included, Alzheimer’s disease (AD), Parkinson’s disease (PD), and multiple sclerosis (MS). We discuss the potential for these biomarkers to be used in humans with suspected NDD as prognostic, diagnostic, or monitoring tools, identify knowledge gaps in literature, and propose potential approaches to further elucidate the role of myeloid cells in neurodegeneration and better utilize myeloid biomarkers in the understanding and treatment of NDD.